Polybrominated diphenyl ethers (PBDEs) and indicator polychlorinated biphenyls (PCBs) in various marine fish from Zhoushan fishery, China. (September 2016) - Shang, Xiaohong; Dong, Guixian; Zhang, Hongxia; Zhang, Lei; Yu, Xinwei; Li, Jingguang; Wang, Xiangyong; Yue, Bing; Zhao, Yunfeng; Wu, Yongning
Abstract: Levels of polybrominated diphenyl ethers (PBDEs) and indicator polychlorinated biphenyls (indicator-PCBs) were measured in thirty-two commonly consumed marine fish species from Zhoushan Fishery, China. Factors effecting the accumulation of the compounds in sea fish were discussed, as well as the associated health risk via fish consumption. Levels and congener profiles of these contaminants varied by fish type. Due to the different accumulation influenced by fat content, feed habits and living zone in the sea area, levels of total nine PBDEs ranged from 0.0085 ng/g wet weight (Pagrosomus major) to 1.6819 ng/g wet weight (Bullet mackerel). The corresponding values for six indicator-PCBs ranged from 0.0124 ng/g wet weight ( Navodon septentrionalis) to 3.8244 ng/g wet weight ( Bullet mackerel ). Total PBDEs and total indicator-PCBs intakes for Chinese population were estimated according to the contaminant level in each fish species and mean fish consumption in China, using an average body weight as 60 kg for the general population. The estimated intake of total PBDEs and total indicator-PCBs ranged from 0.007 ng/kg bw/day ( Pagrosomus major ) to 1.402 ng/kg bw/day ( B . mackerel ) and 0.010 ng/kg bw/day ( N . septentrionalis ) to 3.187 ng/kg bw/day ( B . mackerel ), respectively. The evaluated health risk associated with PBDEs intakes and indicator-PCBs intakes via consumption of all the fish species are relatively low for Chinese resident. Highlights: 32 Fish species were measured for polybrominated diphenyl ethers and indicator polychlorinated biphenyls. Factors effecting the accumulation of the compounds in sea fish were discussed. The associated health risk via fish consumption was assessed.